CGAS is activated by DNA in a length‐dependent manner. (11th August 2017) - Luecke, Stefanie; Holleufer, Andreas; Christensen, Maria H; Jønsson, Kasper L; Boni, Gerardo A; Sørensen, Lambert K; Johannsen, Mogens; Jakobsen, Martin R; Hartmann, Rune; Paludan, Søren R
Abstract: Cytosolic DNA stimulates innate immune responses, including type I interferons (IFN), which have antiviral and immunomodulatory activities. Cyclic GMP‐AMP synthase (cGAS) recognizes cytoplasmic DNA and signals via STING to induce IFN production. Despite the importance of DNA in innate immunity, the nature of the DNA that stimulates IFN production is not well described. Using low DNA concentrations, we show that dsDNA induces IFN in a length‐dependent manner. This is observed over a wide length‐span of DNA, ranging from the minimal stimulatory length to several kilobases, and is fully dependent on cGAS irrespective of DNA length. Importantly, in vitro studies reveal that long DNA activates recombinant human cGAS more efficiently than short DNA, showing that length‐dependent DNA recognition is an intrinsic property of cGAS independent of accessory proteins. Collectively, this work identifies long DNA as the molecular entity stimulating the cGAS pathway upon cytosolic DNA challenge such as viral infections. Synopsis: Cytosolic DNA stimulates innate immunity via cGAS‐STING signaling. The response to dsDNA depends on DNA length at physiological DNA concentrations. Activation of cGAS occurs more efficiently with long DNA. This preference is an intrinsic property of cGAS. cGAS‐mediated type I IFN production is dependent on DNA length. The length‐dependency is seen at low DNA concentrations comparable with infections. Recombinant human cGAS produces cGAMP in a DNA length‐dependent manner in vitro . Abstract : Cytosolic DNA stimulates innate immunity via cGAS‐STING signaling. The response to dsDNA depends on DNA length at physiological DNA concentrations. Activation of cGAS occurs more efficiently with long DNA. This preference is an intrinsic property of cGAS.